LC-MS/MS-based proteomics and metabolomics of HCT-116 colorectal cancer cells: A potential anticancer activity of atorvastatin - Refat M. Nimer; Hiba A. Nazazleh; Belal A. Al-Husein; Salah Abdelrazig; Lina Elsalem; Lina A. Dahabiyeh (Pharmacia)
Colorectal cancer (CRC) is the third most prevalent tumor in men, the second most common in women, and the fourth leading cause of mortality worldwide. Statins reduce cholesterol levels by hampering the function of 3-hydroxy-3-methyl-glutaryl-CoA reductase enzymes in cholesterol synthesis. Strains have shown anticancer effects against CRC. However, statins’ anticancer mechanism is yet unknown. Liquid chromatography–mass spectrometry (LC–MS)-based untargeted metabolomics and proteomics were employed to study statins’ effects on CRC using the CRC cell line HCT-116. These approaches were utilized to identify potential underlying metabolic pathways and proteins altered in atorvastatin (a statin)-treated HCT-116 cells. Compared to the control, atorvastatin significantly altered numerous metabolites in HCT-116 cells, including a reduction in the levels of decanoylcarnitine and octanoyl-L-carnitine and in the biosynthesis and metabolism of amino acids like alanine and citrate cycle. Proteomic study showed that atorvastatin-treated HCT-116 cells expressed 127 proteins differently from controls. Novel findings were among them, such as centromere-associated protein E, cytochrome c oxidase subunit 6A1 mitochondrial, and hyaluronan synthase 1. The findings indicate that atorvastatin may have potential anticancer characteristics and highlight the essential role metabolomics and proteomics to understand complex metabolic pathways and proteins relevant to cancer and develop novel treatment targets.